(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Setiawan A, Siregar VP, Susilo SB, Mardiastuti A, Agus SB. 2022. Geomorphological classification of benthic structures of Kaledupa Atoll Wakatobi National Park, Indonesia. Biodiversitas 23: 3784-3792. Geomorphological mapping is one solution to understanding the complexity of the seabed pattern. This research aims to map the benthic structure of Kaledupa Atoll using the Remote Sensing and Geographic Information System with the Benthic Terrain Modeler (BTM) extension. The data used is in situ bathymetry data using Mapsounder 585 and Sentinel 2A satellite image data downloaded for free. BTM is a technique for examining benthic habitat and shallow water geomorphology. BTM was used to analyze integrated depth data to determine the bathymetric position index (BPI), slope, and classification of reef geomorphological structures. Thirteen structural classes of habitat geomorphology resulting from this research are Flat plain with the largest area of ??17142.35 ha, and the class with the smallest area is Crevices class, with narrow gullies rock outcrops 1.64 ha. While the other classes in a row are Broad slope 9104.53 ha; Flat ridge tops, upper slopes 4262.67 ha; Current scoured depressions on a slope 3420.98 ha; Narrow depressions at the base of rock outcrops 2348.20 ha; Rock outcrop highs, narrow ridges 1792.45 ha; Local ridges, boulders, pinnacles on slopes 879.29 ha; Scarp, cliff or small local depressions on a slope 703.02 ha; Local ridges, boulders, pinnacles on broad flat 490.17 ha; Local depressions, current scoured on flat 416.39 ha; Local ridges, boulders, pinnacles on broad depressions 16.63 ha; and Steep slopes 2.88 ha.